Changes in nutrient balance, methane emissions, physiologic biomarkers, and production performance in goats fed different forage-to-concentrate ratios during lactation. (13th April 2021) - Fernández, Carlos; Hernández, Alberto; Gomis-Tena, Julio; Loor, Juan J
Abstract: The objective was to determine the effect forage-to-concentrate (F:C ) ratio and stage of lactation on methane emissions, digestibility, nutrient balance, lactation performance, and metabolic responses in lactating goats. Twenty Murciano-Granadina dairy goats were used in an experiment divided into 3 periods: early (30 d), mid (100 d), and late (170 d) lactation. All goats were fed a diet with 35:65 F:C (FCL ) during early-lactation. Then, 1 group ( n = 10 goats) remained on FCL through mid- and late-lactation while the other group ( n = 10 goats) was fed a diet with 50:50 F:C at mid-lactation (FCM ) and 65:35 (FCH ) at late lactation. A greater proportion of concentrate in the diet was associated with greater overall intake and digestibility ( P < 0.05). Energy balance was negative in early-lactation (−77 kJ/kg of BW 0.75, on average) and positive for FCL at mid- and late-lactation (13 and 35 kJ/kg of BW 0.75, respectively). Goats fed FCM and FCH maintained negative energy balance throughout lactation. Plasma concentrations of non-esterified fatty acids at mid-lactation were greater for FCM than FCL (680 mEq/L), and at late-lactation concentrations were greater for FCH and FCL (856 mEq/L). A similar response was detected for plasma β-hydroxybutyrate. Methane emission was greater ( P < 0.05) for FCM than FCH (1.7 g CH4 /d). This study demonstrated that differences in F:C across stages of lactation lead to distinct metabolic responses at the level of the rumen and tissues.